PROBLEM ARISING FROM NEW TECHNOLOGY ON E-GOVERNMENT, THE USE OF HAY.U APPLICATION IN BANDUNG, INDONESIA - Abdullah Ramdhani; Dini Turipanam Alamanda; Ai Miman Nurdiaman; Muhammad Arief (Jurnal Manajemen Indonesia, 2019)
This study aims to discover what has been done by BPPT Bandung in making the implementation the strategy of Integrated Licensing Services Agency to make Hay.U application Bandung to be effective. The factors used to analyze it is PIECES consisting of performance, information, efficiency, control, economy, and service. Using a qualitative approach, interviews with a number of stakeholders were conducted to get a comprehensive overview of the application which presently becomes the mainstay of Bandung city government. The results of this study reveal that Hay.U can overall support the performance of users and employees. In addition, Hay. U is also able to improve the accuracy of information which can make online licensing system in Bandung effective. However, the Integrated Licensing Service Agency (BPPT) needs to consider the convenience factor for the users when inputting data. Users still have problems with the new technology and the amount of data needing to be attached. Keywords — E-Government, Online system, Web-based Application. AbstrakPenelitian ini bertujuan untuk mengetahui apa yang telah dilakukan oleh BPPT Bandung dalam mengimplementasikan strateginya untuk menjadikan aplikasi Hay.U Bandung menjadi efektif. Faktor yang digunakan untuk menganalisis data adalah PIECES yang terdiri dari kinerja (performance), informasi (information), efisiensi (efficiency), control (control), ekonomi (economic), dan layanan (service). Dengan menggunakan pendekatan kualitatif, wawancara dengan sejumlah pemangku kepentingan dilakukan untuk mendapatkan gambaran komprehensif dari aplikasi yang saat ini menjadi andalan pemerintah kota Bandung. Hasil penelitian ini mengungkapkan bahwa Hay.U secara keseluruhan dapat mendukung kinerja pengguna dan karyawan. Selain itu, Hay. U juga dapat meningkatkan keakuratan informasi yang dapat membuat sistem lisensi online di Bandung efektif. Namun, BPPT perlu mempertimbangkan faktor kenyamanan bagi pengguna saat memasukkan data. Pengguna masih memiliki masalah dengan penerimaan teknologi baru dan banyaknya data yang perlu dilampirkan. Kata Kunci—E-Government, Sistem daring , Aplikasi Berbasis Web.